Public sector accountants and quantum leap : how far we can survive in Industrial Revolution 4.0? : proceedings of the 1st International Conference on Public Sector Accounting (ICOPSA 2019), October 29-30, 2019, Jakarta, Indonesia /: how far we can survive in Industrial Revolution 4.0? : proceedings of the 1st International Conference on Public Sector Accounting (ICOPSA 2019), October 29-30, 2019, Jakarta, Indonesia. (2020) - Unknown
No abstract available